Clean and Healthy Living Behavior to Prevent Acute Respiratory Infection among Farmer's Families - Enggal Hadi Kurniyawan; Ahmad Hykal Adlan Zein; Selvia Amelinda Novianti; Ivada Dea Nintiarso; Kholid Rosyidi Muhammad Nur; Dicky Endrian Kurniawan; Alfid Tri Afandi; Ida Zuhroidah (KHD Production, 2024)
Acute Respiratory Infection (ARI) cases in Indonesia and abroad are still a significant health problem. In Indonesia, ARI ranks first as a cause of death in infants and toddlers, with a mortality rate of around 20-30%. ARI can cause severe breathing difficulties, such as pneumonia, and ARI is also one of the leading causes of death in children under the age of five in developing countries. This study aims to analyze how to improve clean and healthy living behavior to prevent ARI in farmer families. The research method used was a literature review conducted through Google Scholar, PubMed, and Science Direct in the 2019-2024 range. The keywords used in the search for articles were